Staging Monoclonal Plasma Cell Disease: Comparison of the Durie-Salmon and the Durie-Salmon PLUS Staging Systems - Fechtner, Kerstin; Hillengaß, Jens; Delorme, Stefan; Heiß, Christiane; Neben, Kai; Goldschmidt, Hartmut; Kauczor, Hans-Ulrich; Weber, Marc-André (Radiology, 2010)
Purpose - - To investigate the concordance of the Durie-Salmon staging system with the Durie-Salmon PLUS staging system in monoclonal plasma cell disease. - - Materials and Methods - - Institutional review board approval was obtained, with waiver of informed consent. Lesions in 403 untreated patients (age range, 21-83 years) with monoclonal gammopathy of undetermined significance (MGUS) (n = 84), solitary plasmacytoma (n = 17), amyloid light-chain amyloidosis (n = 12), and multiple myeloma (MM) (n = 290) were first staged on the basis of the classic Durie-Salmon staging system, which included conventional radiography. After examination with whole-body (WB) magnetic resonance (MR) imaging, lesions in these patients were, in addition, staged by using the Durie-Salmon PLUS staging system. Bone marrow infiltration pattern and focal lesions described as intramedullary, transcortical, and soft-tissue lesions, were assessed. The staging levels of both systems were compared. - - Results - - Of 84 patients with MGUS, lesions in 33 (39%) would have been staged differently with Durie-Salmon PLUS staging system when compared with Durie-Salmon staging system (stage I MM [37%], stage II MM [0%], and stage III MM [2%]). All 17 patients with plasmacytoma showed additional focal lesions or a diffuse infiltration leading to a classification as stage I MM (76%), stage II MM (12%), or stage III MM (12%) with Durie-Salmon PLUS. Of the 149 patients with stage I MM, lesions in 81 (54%) would have been staged differently with the Durie-Salmon PLUS staging system. Of the 21 patients with stage II MM, lesions in 19 (91%) would have been staged differently with Durie-Salmon PLUS staging system when compared with the Durie-Salmon staging system. Of the 120 patients with stage III MM, lesions in 72 (60%) would have been staged differently with the Durie-Salmon PLUS staging system. - - Conclusion - - Given the fact that the Durie-Salmon and Durie-Salmon PLUS staging systems were concordant in only 45% of all examined patients with monoclonal plasma cell disease, in most cases, treatment decisions depend on the staging system used and, thus, remain a matter of debate. - - © RSNA, 2010